IMPLEMENTASI APLIKASI QUIZIZZ DALAM MENINGKATKAN MOTIVASI BELAJAR PESERTA DIDIK PADA MATA PELAJARAN PENDIDIKAN PANCASILA DAN KEWARGANEGARAN - Syahabuddin, Syahabuddin; Kesuma, Sapta; Gultom, Rumesti (Center for Research and Community Service (LPPM) University of Abulyatama, 2025)
Students' learning motivation is very important in the learning process because it is one of the factors that determines whether students can achieve achievements. One way to keep students' learning motivation good in learning is by using learning media in the learning process. This research aims to find out how Pancasila and Citizenship Education subject teachers apply the Quizizz application as a learning medium in the learning process as an effort to increase students' learning motivation. This research is a case study research using a qualitative approach carried out at SMA Negeri 14 Medan. The results of this research show that the application of the Quizizz application as a learning medium by Civics subject teachers has gone very well, where all students can understand well the procedures for using Quizizz. Using Quizizz can also facilitate better learning through its interactive and competitive features, such as interesting online quizzes, automatic leaderboards, immediate feedback, and game elements that can motivate students to participate actively